Sweet Solutions for Analgesia in Neonates in China: A Systematic Review and Meta-Analysis. Issue 2 (June 2019) - Huang, Rui-Rui; Xie, Ri-Hua; Wen, Shi Wu; Chen, Shao-Lin; She, Qin; Liu, Yan-Nan; Harrison, Denise
Introduction: High-quality synthesized evidence of sweet taste analgesia in neonates exists. However, Chinese databases have never been included in previous systematic reviews of sweet solutions for procedural pain. Objective: To conduct a systematic review of Chinese literature evaluating analgesic effects of sweet solutions for neonates. Data sources: Wang Fang, China National Knowledge Infrastructure and Chinese Biomedical Literature Database. Data extraction and analysis: Two authors screened studies for inclusion and conducted risk of bias ratings and data extraction. A third author resolved any conflicts. Meta-analyses were performed using RevMan 5.2 software, on mean differences in pain outcomes using random effects models. Results: Thirty-one trials (4999 neonates) were included; 26 trials used glucose, 4 used sucrose, and 1 trial evaluated both solutions. Sweet solutions reduced standardized mean pain scores (n = 21 studies; −1.68, 95% confidence interval −2.08, −1.27) and cry duration (n = 6 studies; −25.60, 95% confidence interval −36.47, −14.72 s) but not heart rate change (n = 7 studies; −17.64, 95% confidence interval −52.71, 17.43). No included studies cited the previously published systematic reviews of sweet solutions. Conclusions: This systematic review of Chinese databases showed the same results as previously published systematic reviews. No trials included in this review cited the English systematic reviews, highlighting a parallel research agenda.